2000
DOI: 10.1016/s0002-9440(10)64532-4
|View full text |Cite
|
Sign up to set email alerts
|

Antineutrophil Cytoplasmic Antibodies Induce Reactive Oxygen-Dependent Dysregulation of Primed Neutrophil Apoptosis and Clearance by Macrophages

Abstract: This study assessed whether anti-neutrophil cytoplasmic antibodies (ANCAs) interfere with the safe deletion of neutrophils by apoptosis and phagocytic clearance. Tumor necrosis factor (TNF)-primed neutrophils were incubated with normal IgG (N IgG) or ANCA IgG for up to 36 hours. Compared with N IgG, ANCAs accelerated constitutive apoptosis of TNF-␣ primed neutrophils, as assessed by morphology and confirmed by DNA laddering pattern on gel electrophoresis, and accelerated progression to secondary necrosis. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
66
0
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(69 citation statements)
references
References 51 publications
1
66
0
2
Order By: Relevance
“…The data also did not support the contention that ANCAs may help perpetuate an immune response through their previously demonstrated effects on accelerating neutrophil apoptosis. ANCAs induce accelerated and dysregulated apoptosis of TNF␣-primed neutrophils, resulting in a reduced likelihood of recognition and phagocytosis by macrophages before disintegration through secondary necrosis (30). However, uptake of secondarily necrotic neutrophils by DCs led to a reduced, not enhanced, capacity of DCs to stimulate an MLR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The data also did not support the contention that ANCAs may help perpetuate an immune response through their previously demonstrated effects on accelerating neutrophil apoptosis. ANCAs induce accelerated and dysregulated apoptosis of TNF␣-primed neutrophils, resulting in a reduced likelihood of recognition and phagocytosis by macrophages before disintegration through secondary necrosis (30). However, uptake of secondarily necrotic neutrophils by DCs led to a reduced, not enhanced, capacity of DCs to stimulate an MLR.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils were cultured at 37 o C for 18 hours, after which 80 Ϯ 1.4% of the cells (mean Ϯ SEM) were apoptotic as assessed by morphologic analysis using Jenner-Giemsa (BDH, Poole, UK) staining of cytospins. Apoptosis was confirmed by staining for annexin V (30,34). Fewer than 5% of cells were necrotic as assessed by trypan blue dye exclusion and propidium iodide incorporation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, apoptotic cells can amplify local inflammatory processes as a result of secondary necrosis. 6,7 Recent studies showed that all apoptotic cells within plaques such as lymphocytes, monocytes, and smooth muscle and endothelial cells may acquire procoagulant potential, 8 -10 probably by activating tissue factor 11 after the exposure to phosphatidylserine inside the exoplasmic leaflet of the plasma membrane. Furthermore, membrane microparticles shed by fragmented apoptotic cells also have procoagulant properties.…”
mentioning
confidence: 99%
“…For example, heat-accelerated apoptosis could result in proinflammatory removal of apoptotic neutrophils, particularly when these apoptotic cells become opsonized with ANCAs (30)(31)(32). However, other investigators have found that, based on observations in animal and human studies, fever is beneficial in host defense reactions, and also that antipyretic treatment interferes with this effect (19)(20)(21)33).…”
mentioning
confidence: 99%